1997
DOI: 10.1007/s005850050549
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous observations of the 2-day wave at London (43°N, 81°W) and Saskatoon (52°N, 107°W) near 91 km altitude during the two years of 1993 and 1994

Abstract: Abstract. Simultaneous observations are valuable in providing further insights into the character of the quasi 2-day wave. In this study we investigate the period and amplitude for the quasi 2-day wave near 91 km using MF radars at London and Saskatoon, Canada, and in addition look at possible values of the zonal wave number. The results of the present study bring out certain new aspects of the quasi 2-day wave at midlatitudes in the Northern Hemisphere. In particular we show that the period of the quasi 2-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…For example, Harris and Vincent [1993] based on MF radar data at Christmas Island (2°N, 157°W) between 80 and 100 km over ∼2 years from January 1990 to April 1992 reported that the median periods are between 48 and 52 hours, and wave periods are near 50 hours in July/August and near 48 hours in January/February. However, Thayaparan et al [1997] based on simultaneous observations at London (43°N, 81°W) and Saskatoon (52°N, 107°W) near 91 km over 2 years in 1993 and 1994 showed that the period of the Q2DW determined is smaller (46–47 hours) than the 51–52 hour period often suggested previously, and that the periods showed variability as a function of time. Clark et al [1994] also preferred the 48‐hour period.…”
Section: Discussionmentioning
confidence: 62%
“…For example, Harris and Vincent [1993] based on MF radar data at Christmas Island (2°N, 157°W) between 80 and 100 km over ∼2 years from January 1990 to April 1992 reported that the median periods are between 48 and 52 hours, and wave periods are near 50 hours in July/August and near 48 hours in January/February. However, Thayaparan et al [1997] based on simultaneous observations at London (43°N, 81°W) and Saskatoon (52°N, 107°W) near 91 km over 2 years in 1993 and 1994 showed that the period of the Q2DW determined is smaller (46–47 hours) than the 51–52 hour period often suggested previously, and that the periods showed variability as a function of time. Clark et al [1994] also preferred the 48‐hour period.…”
Section: Discussionmentioning
confidence: 62%
“…The interaction between a PW with frequency Δ and zonal wave number m, i.e., cos(Δ t + m − Φ n,s ), with a tide with frequency nΩ and zonal wave number s, cos(nΩt + s ), thus yields sum and difference secondary waves (hereafter SW + and SW − ), with frequencies nΩ ± Δ and zonal wave numbers s ± m. In the spectrum of a time series, long-period PW (Δ << nΩ) appears as two sideband peaks on either side of the main tidal peak at frequency nΩ. A well-documented example is modulation of the migrating (Sun-synchronous, westward propagating) semidiurnal tide (n = 2, s = 2) with the westward propagating quasi-2 day wave QTDW (n = 0.5, s = 3) [Cevolani and Kingsley, 1992;Beard et al, 1999;Manson et al, 1982;Harris and Vincent, 1993;Thayaparan et al, 1997aThayaparan et al, , 1997bPalo et al, 1999]. The SWs are a westward propagating 9.6 h wave with s = 5 and an eastward propagating 16 h wave with s = −1; the zonal wave numbers obviously cannot be differentiated using ground-based observations.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature amplitudes can reach up to about 11 K in the altitude range 80-100 km [e.g., Limpasuvan and Wu, 2003]. In the upper mesosphere, wind amplitudes can be up to about 50 m/s in the meridional wind at low latitudes [e.g., Fritts et al, 1999], and up to about 30 m/s in the zonal wind at middle latitudes [e.g., Thayaparan et al, 1997]. Signatures of the QTDW are also found in atmospheric constituent data [e.g., Azeem et al, 2001].…”
Section: Introductionmentioning
confidence: 99%